Near-surface-mounted retrofitting of damaged/undamaged adobe walls using steel bars: Analytical evaluation of experimental results. (December 2020) - Mirabi Banadaki, Hosein; Eslami, Abolfazl; Ronagh, Hamid
Abstract: This study examines the results of an extensive experimental program pertaining to seismic strengthening of adobe walls using near-surface-mounted (NSM) steel bars. The experiments were conducted on seven adobe wall panels ( 1020 × 800 × 200 m m ) subjected to the combined action of vertical pre-compression stresses (0.1 and 0.3 MPa) and incremental lateral loading reversals. The parameters investigated included NSM reinforcement ratio, level of vertical stress, and pre-existing damage. The load–displacement curves obtained from pushover tests were employed in the seismic evaluations using a capacity spectrum approach called the N2 method. Based on the experimental and analytical findings, the adopted retrofitting technique was found capable of effectively enhancing the in-plane seismic performance of both the undamaged and damaged adobe walls in terms of lateral strength, displacement capacity, energy dissipation, and the tolerated peak ground acceleration. It was found that the retrofitting intervention has a more beneficial contribution to the displacement capacity, rather than lateral resistance, of adobe walls under high axial pre-compression loads. Finally, analytical models originally developed for masonry walls were modified for estimating the in-plane lateral resistance of reinforced/unreinforced adobe walls.